The Role of Video Capsule Endoscopy in Overt Gastrointestinal Bleeding - Dedy Gunawanjati Sudrajat; Florencia Pauliana Wijanarko (Cermin Dunia Kedokteran, 2017)
Overt gastrointestinal (GI) bleeding is defined as visible GI bleeding (melena and hematochezia) and can be categorized further as active versus inactive bleeding. Endoscopy is routinely used to find the cause of bleeding, but small bowel has been largely inaccessible by this conventional endoscopy. Video capsule endoscopy (VCE) is one of methods that can reach the small bowel. We report a 45-year old woman with recurrent hematochezia. She had previous hematochezia 4 years ago, but no definite diagnosis was concluded. We performed esophagogastroduodenoscopy (EGD) and colonoscopy. We found gastritis and colonic diverticulosis, but no site of active bleeding. Video capsule endoscopy showed no source of bleeding in the small bowel.Perdarahan saluran cerna yang nyata (overt) adalah perdarahan saluran cerna yang dapat dilihat mata telanjang (melena atau hematochezia), dapat merupakan perdarahan aktif atau inaktif. Endoskopi rutin digunakan untuk mencari sumber perdarahan saluran cerna, namun usus halus merupakan bagian yang tidak terjangkau. Video kapsul endoskopi adalah salah satu metode yang mampu menjangkau usus halus. Kami melaporkan kasus wanita 45 tahun hematochezia berulang. Riwayat hematochezia sebelumnya 4 tahun yang lalu namun belum didiagnosis. Pada gastroskopi dan kolonoskopi ditemukan gastritis dan divertikel kolon, namun tidak ditemukan perdarahan aktif. Video kapsul endoskopi tidak menemukan sumber perdarahan dari usus halus.